Belonging to the Land in Tura: Reforms, Migrations, and Indentity Politics in Evenkia - Olga Povoroznyuk (Journal of Ethnology and Folkloristics)
Tura is a mixed community where Evenks live alongside other indigenous groups and Russians. The establishment of Evenk autonomy, with the centre in Tura, in 1930 strengthened Evenk ethnic identity and unity through increased political and cultural representation, as well as through the integration of migrants from other regions. In the post-Soviet period, the community witnessed a population loss, a declining socio-economic situation, and the abolition of autonomy. In the long course of reforms and identity construction, the indigenous intelligentsia has manipulated the concept of belonging to the land either to stress or to erase cultural differences, and thus, to secure the access of the local elite to valuable resources. currently, the most hotly debated boundaries are those dividing Evenks into local and migrant, authentic and unauthentic, urban and rural. The paper illustrates the intricate interrelations between ethnic, indigenous, and territorial identities from an identity politics perspective.